Fenomena Lunturnya 3 Makna Kata (Tolong, Maaf dan Terimakasih) dalam Etika Komunikasi di Kota Medan - Pohan, Syafruddin; Ariftha, Annisa; Ramadhan, All Rizky; Afif, Ahmad Saleh (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The city of Medan, as a center of rapidly developing social and economic activity, is experiencing an interesting phenomenon related to the erosion of the meaning of words in communication ethics, namely